GANDHIAN PERSPECTIVE ON THE DEVELOPMENT OF RURAL WOMEN (International Journal of Food and Nutritional Sciences, 2022)
Mahatma Gandhi perspective on the development of rural women was multifaceted, emphasizing education, economic independence, political participation, health, self-reliance, and nonviolent activism. His vision aimed to create a more equitable and just society by recognizing and harnessing the potential of women as drivers of positive change. Gandhiji thought about the importance of women power and their responsibility in shaping the course of history and progress. Mahatma Gandhi asserted that women are indistinguishable from men in all their praise and can assume responsibilities with corresponding dexterity and efficiency. Gandhiji saw man and woman as two sides of the same coin and synchronized each other. Gandhi did not see himself as a prophet but as a practical optimist.